Eye contact with neutral and smiling faces: effects on autonomic responses and frontal EEG asymmetry - Pönkänen, Laura M.; Hietanen, Jari K. (Frontiers in Human Neuroscience, 2012)
In our previous studies we have shown that seeing another person “live” with a direct vs. averted gaze results in greater relative left-sided frontal asymmetry in the electroencephalography (EEG), associated with approach motivation, and in enhanced skin conductance responses indicating autonomic arousal. In our studies, however, the stimulus persons had a neutral expression. In real-life social interaction, eye contact is often associated with a smile, which is another signal of the sender’s approach-related motivation. A smile could therefore enhance the affective-motivational responses to eye contact. In the present study, we investigated whether the facial expression (neutral vs. smile) would modulate the frontal EEG asymmetry and autonomic arousal to seeing a direct vs. an averted gaze in faces presented “live” through a liquid crystal shutter. The results showed that the skin conductance responses were greater for the direct than the averted gaze and that the effect of gaze direction was more pronounced for a smiling than a neutral face. However, the frontal EEG asymmetry results revealed a more complex pattern. Participants whose responses to seeing the other person were overall indicative of leftward frontal activity (indicative of approach) showed greater relative left-sided asymmetry for the direct vs. averted gaze, whereas participants whose responses were overall indicative of rightward frontal activity (indicative of avoidance) showed greater relative right-sided asymmetry to direct vs. averted gaze. The other person’s facial expression did not have an effect on the frontal EEG asymmetry. These findings may reflect that another’s direct gaze, as compared to their smile, has a more dominant role in regulating perceivers’ approach motivation.